Illness Representations of HIV Positive Patients Are Associated with Virologic Success - Leone, Daniela; Borghi, Lidia; Lamiani, Giulia; Barlascini, Luca; Bini, Teresa; d’Arminio Monforte, Antonella; Vegni, Elena (Frontiers in Psychology, 2016)
Introduction: It is important for HIV positive patients to be engaged in their care and be adherent to treatment in order to reduce disease progression and mortality. Studies found that illness representations influence adherence trough the mediating role of coping behaviours. However, no study has ever tested if patient engagement to the visits mediate the relationship between illness perceptions and adherence. This study aimed to explore illness representations of HIV positive patients and test the hypothesis that illness representations predict adherence through the mediating role of a component of behavioral engagement. Methods: HIV-positive patients treated with HAART for at least one year and presenting to a check-up visit were eligible to participate in the study. Patients completed the Illness Perception Questionnaire-Revised. Behavioural engagement was measured based on the patients’ clinical attendance to the check-up visits; adherence to HAART was measured by viral load. Undetectable viral load or HIV-RNA <40 copies/ml were considered indexes of virologic success. Results: A total of 161 patients participated in the study. Most of them coherently attributed the experienced symptoms to HIV/HAART; perceived their condition as chronic, stable, coherent, judged the therapy as effective, and attributed their disease to the HIV virus and to their behaviour or bad luck. The majority of patients (80.1%) regularly attended check-up visits and 88.5% of them reached virologic success. The mediation model did not show good fit indexes. However, a significant direct effect of two independent variables on virologic success was found. Specifically, the perception that the disease does not have serious consequences on patient’s life and the prevalence of negative emotions towards HIV were associated with virologic success. On the contrary, the patient’s perception that the disease has serious consequences on his/her life and the prevalence of positive emotions were associated with virologic failure. This model showed good fit indexes (CFI=1; TLI=1; RMSEA=0.00; WRMSR=0.309). Discussion: Results do not support the mediating role of behavioural engagement in the relationship between illness representations and adherence. As perception of serious consequences coupled with positive emotions are directly associated with virologic failure, clinicians should take them into account to promote treatment adherence.